Acid–base responsive photoluminescence switching of CdSe/ZnS quantum dots coupled to plasmonic gold film using nanometer-thick poly[(2-diethylamino)ethyl methacrylate] layer. Issue 34 (16th August 2022) - Moradi, Maryam; Staude, Isabelle; Pertsch, Thomas; Jäger, Michael; Schubert, Ulrich S.
Abstract : Control of plasmon–nanoemitter interaction at nanoscale by a pH responsive intermediate layer of poly[(2-diethylamino)ethyl methacrylate] enables the modulation of photoluminescence intensity of nanoemitters, being an appealing switchable system. Abstract : The control of plasmon–nanoemitter interactions at the nanoscale enables the tailored modulation of optical properties, namely, the photoluminescence (PL) intensity of the nanoemitters. In this contribution, using a nanometer-thick poly[(2-diethylamino) ethyl methacrylate] (39 to 74 nm) as pH responsive spacer layer (p K a ∼ 6 to 6.5) between a plasmonic gold film and CdSe/ZnS Quantum Dots (QDs) nanoemitters, we could achieve reversible pH-responsive PL switching in QDs. In fact, the swelling (at pH 5) and shrinking (at pH 11) function of the pH-responsive spacer layer modulates the distance between the QDs and the gold surface, which dictates the plasmonic film–QDs nanoemitter interaction. Notably, we observed a high QDs' PL enhancement of up to a factor of 3.1 ± 0.4 through changing the pH value from 5 to 11. Furthermore, based on a systematic analysis of several samples with different spacer layer thicknesses and multiple pH cycles, our developed system revealed substantial stability, reversibility and PL enhancement reproducibility. Thus, the established acid–base responsive switchable systems may represent an appealing platform for applications such as sensors, biochemical assays, optoelectronics and logic gates and can be easily evolved to other multifunctional switchable systems using alternative stimuli-responsive polymers.